The Ovaherero/Nama Genocide: A Case for an Apology and Reparations - Sprenger, Nick; Rodriguez, Robert G.; Kamaṱuka, Ngondi A. (European Scientific Journal, ESJ, 2017)
This research examines the consequences of the Ovaherero and Nama massacres occurring in modern Namibia from 1904-08 and perpetuated by Imperial Germany. Recent political advances made by, among other groups, the Association of the Ovaherero Genocide in the United States of America, toward mutual understanding with the Federal Republic of Germany necessitates a comprehensive study about the event itself, its long-term implications, and the more current vocalization toward an apology and reparations for the Ovaherero and Nama peoples. Resulting from the Extermination Orders of 1904 and 1905 as articulated by Kaiser Wilhelm II’s Imperial Germany, over 65,000 Ovaherero and 10,000 Nama peoples perished in what was the first systematic genocide of the twentieth century. This study assesses the historical circumstances surrounding these genocidal policies carried out by Imperial Germany, and seeks to place the devastating loss of life, culture, and property within its proper historical context. The question of restorative justice also receives analysis, as this research evaluates the case made by the Ovaherero and Nama peoples in their petitions for compensation. Beyond the history of the event itself and its long-term effects, the paper adopts a comparative approach by which to integrate the Ovaherero and Nama calls for reparations into an established precedent.